I've looked into WolframAlpha and deduced from some examples that:

$$ \sum_{n=k}^{\infty} \frac{1}{ \binom{n}{k}} = \frac{k}{k-1} ~~~~ \text{where} ~~~ k \in \mathbb{N} \setminus \{1\}$$

But why is that? The only thing I could pull of is this:

$$ \sum_{n=k}^{\infty} \frac{1}{ \binom{n}{k}} = \sum_{n=k}^{\infty} \frac{k! (n-k)!}{n!} = k! \sum_{n=k}^{\infty} \frac{ (n-k)!}{n!} = k! \sum_{n=k}^{\infty} \frac{1}{(n-k+1) \cdot (n-k+2)\dots \cdot n}$$

Which then got me into a dead-end (for my knowledge) ... I am curious as why is that and but this actually mean "combinatorically" / "statistically" and how to actually evaluate this.


  • 1
    $\begingroup$ Does the series telescope? $\endgroup$ Sep 17, 2020 at 2:13
  • 1
    $\begingroup$ Perhaps you've seen something like $\sum_{n=2}^{\infty}\frac{1}{n(n-1)}=1$, using partial fractions on the summands and then telescoping (often used as an example in calculus courses). Try $k=3,4$ and see what happens. $\endgroup$
    – yoyo
    Sep 17, 2020 at 2:21

3 Answers 3


$$ \begin{align} \sum_{n=k}^\infty\frac1{\binom{n}{k}} &=\sum_{n=k}^\infty\frac{k!}{n(n-1)\cdots(n-k+1)}\tag1\\ &=\sum_{n=k}^\infty\frac{k!}{k-1}\left({\scriptsize\frac{n}{n(n-1)\cdots(n-k+1)}-\frac{n-k+1}{n(n-1)\cdots(n-k+1)}}\right)\tag2\\ &=\sum_{n=k}^\infty\frac{k!}{k-1}\left({\scriptsize\frac1{(n-1)(n-2)\cdots(n-k+1)}-\frac1{n(n-1)\cdots(n-k+2)}}\right)\tag3\\ &=\sum_{n=k}^\infty\frac{k}{k-1}\left({\scriptsize\frac{(k-1)!}{(n-1)(n-2)\cdots(n-k+1)}-\frac{(k-1)!}{n(n-1)\cdots(n-k+2)}}\right)\tag4\\ &=\sum_{n=k}^\infty\frac{k}{k-1}\left(\frac1{\binom{n-1}{k-1}}-\frac1{\binom{n}{k-1}}\right)\tag5\\ &=\frac{k}{k-1}\tag6 \end{align} $$ Explanation:
$(1)$: expand the binomial coefficient
$(2)$: $\frac{n-(n-k+1)}{k-1}=1$
$(3)$: cancel fractions
$(4)$: distribute $(k-1)!$
$(5)$: collect binomial coefficients
$(6)$: the sum telescopes


So the sum you are concerned with is $$\sum_{n=k}^{\infty} \frac{1}{(n-k+1) \cdot (n-k+2)\dots \cdot n}$$ which has the product of $k$ consecutive integers in the denominator of each summand which you can express as the difference of two fractions each with the product of $k-1$ consecutive terms in the denominator. So, for $n=N$, the summand is $$\dfrac{1}{(N-k+1)\cdots(N-1) N}\\ = \dfrac1{k-1}\left(\dfrac{1}{(N-k+1)(N-k+2)\cdots (N-1)}-\dfrac{1}{(N-k+2)\cdots(N-1)N}\right)$$

To get a feel of this fix a $k>2$, say $k=4$, and explicitly write down a few of the summands at the beginning, you should have $$\dfrac1{}+\dfrac1{}+\dfrac1{}+\cdots$$ which using the decomposition mentioned above, becomes $$\frac13\left(\dfrac1{1.2.3}-\dfrac1{2.3.4}\right)+\frac13\left(\dfrac1{2.3.4}-\dfrac1{3.4.5}\right)+\frac13\left(\dfrac1{3.4.5}-\dfrac1{4.5.6}\right)+\cdots$$ do you see what happens if you take $\dfrac1{3}=\dfrac1{k-1}$ common out of all of them?


Use $${n \choose k}^{-1}=(n+1) \int_{0}^{1} x^k (1-x)^{n-k} dx$$ So, $$S=\sum_{n=k}^{\infty} {n \choose k}^{-1}=\sum_{n=k}^{\infty}(n+1)\int_{0}^{1} x^k(1-x)^{n-k} dx=\int_{0}^{1}\sum_{n=k}^{\infty} (n+1) x^k (1-x)^{n-k} dx$$ Let $n-k=p$, then $$S=\int_{0}^{1}x^k dx\sum_{p=0}^{\infty} (p+k+1) (1-x)^p$$ Using $$\sum_{j=0}^{\infty} j~z^{j}=\frac{z}{(1-z)^2}, \sum_{j=0}^{\infty} z^j=\frac{1}{1-z}$$ We get $$S=\int_{0}^{1}\left( \frac{1-x}{x^2}+\frac{1+k}{x}\right) x^k dx=\int(x^{k-2}+k x^{k-1}) dx.$$ Finally, $$S=\frac{k}{k-1}, k\ne 1$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.